Salivary Flow Decreases in Healthy Elderly People Independently of Dental Status and Drug Intake. Issue 4 (10th May 2016) - Vandenberghe‐Descamps, Mathilde; Labouré, Hélène; Prot, Aurélie; Septier, Chantal; Tournier, Carole; Feron, Gilles; Sulmont‐Rossé, Claire
Abstract: In humans, oral food consumption is by far the most important point where food's organoleptic properties can be perceived and can elicit sensory pleasure. It is also the ultimate stage of the food supply chain and the beginning of the food disintegration and digestion process. However, in regard to the influence of ageing on food oral processing, this topic has been mainly investigating through mastication, whereas salivation remains largely unexplored. The present experiment aimed at studying the impact of normal ageing on salivary flow taking into account the dental status and the number of drugs taken by the elderly people. This was achieved by comparing resting and stimulated salivary flows of young versus healthy elderly adults (i.e., autonomous elderly people without acute pathology). Ninety‐three young adults (22–55 years old) and 84 elderly people (70–92 years old) underwent a measurement of resting and stimulated salivary flows and an oral examination (teeth counting; functional unit counting i.e., counting occluding tooth pairs). The present study showed an average 38.5% reduction of resting salivary flow and 38.0% reduction of stimulated salivary flow in healthy elderly people compared to young adults. This reduction was observed independently of the dental status and drug intake: elderly people presented reduced salivary flow even if they did not take any drugs or if their dental status was similar to the one of the young adults. The results also highlight a large inter‐individual variability both in young and elderly adults. Practical Applications: During oral food consumption, saliva plays a key role in the acceptance of food and beverage by modulating the perception of texture, taste and aroma, as well as providing eating comfort by assisting the food breakdown process into a bolus that can be safely swallowed. However, in regard to the influence of ageing on food oral processing, the present results demonstrate a reduced salivary flow in healthy elderly people. Consequently, there is a need for developing foods tailored to the salivary capacities of elderly people aside from the efforts put into the development of foods tailored to the mastication and swallowing abilities of this population. In fact, in the context of an ageing population, the development of products meeting an elderly person's functional capacities becomes a major challenge for the food industry as well as for society.